In-utero Exposure to Violence and Child Health in Iraq - Sulin Sardoschau (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
This paper examines the impact of exposure to violence during pregnancy on anthropometric and cognitive outcomes of children in the medium-run. I combine detailed household-level data on more than 36,000 children with geo-coded information on civilian casualties in the aftermath of the US invasion of Iraq between 2003 and 2009 and exploit within mother differences in prenatal exposure to violence. I find that one violent incident during pregnancy decreases height and weight for age scores by 0.13 standard deviations and lowers cognitive and behavioral skills of children. Leveraging information on the severity, type and perpetrator of violence, I isolate the effect of stress from access to prenatal care. I show that the results hold when restricting attention to incidents with little impact on the local infrastructure and are largest for more stressful events; primarily those that target the civilian population and involve execution and torture.
Keywords: I12; J13; O15; 330; stress; child health; Iraq